2019
DOI: 10.1039/c9ra04999a
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of different electrodeposited NiCo2O4 microspheres anchored on a reduced graphene oxide platform: electrochemical sensor for anti-depressant drug venlafaxine

Abstract: Different electrodeposited NiCo2O4 microspheres supported on a reduced graphene oxide platform for electrochemical sensing of venlafaxine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…This is demonstrated by Ali and El‐Zahry, [119] who have first prepared nickel‐cobalt oxide microspheres using the wet chemistry and in situ electrical deposition, followed by the anchorage of the microspheres on a rGO‐modified graphite electrode. It has been demonstrated that the deposition methods of the microspheres significantly affect the electrochemical behaviour of the generated electrode towards the oxidation of venlafaxine [119] . In addition, the one containing the microspheres generated by using wet chemistry has been found to detect venlafaxine in pharmaceutical formulations and in human plasma, with the detection efficiency not being affected by any co‐existing components [119] .…”
Section: Applications Of Graphene‐based Sensors In Pharmaceutical Ana...mentioning
confidence: 99%
“…This is demonstrated by Ali and El‐Zahry, [119] who have first prepared nickel‐cobalt oxide microspheres using the wet chemistry and in situ electrical deposition, followed by the anchorage of the microspheres on a rGO‐modified graphite electrode. It has been demonstrated that the deposition methods of the microspheres significantly affect the electrochemical behaviour of the generated electrode towards the oxidation of venlafaxine [119] . In addition, the one containing the microspheres generated by using wet chemistry has been found to detect venlafaxine in pharmaceutical formulations and in human plasma, with the detection efficiency not being affected by any co‐existing components [119] .…”
Section: Applications Of Graphene‐based Sensors In Pharmaceutical Ana...mentioning
confidence: 99%
“…Linearity of peak currents vs. root of scan rate in the range of 10-300 mV s À 1 (B) representing diffusion-controlled mechanism of the process. According to Randles-Sevic equation [32], surface area of the electrodes could be calculated by following equation:…”
Section: Surface Area Measurement Of the Electrodesmentioning
confidence: 99%
“…Ali et al comparatively dealt with the utilization of two distinctive deposition methodologies to synthesize NiCo 2 O 4 @rGO-modified graphite electrode [ 39 ]. They used diverse procedures such as EIS, CV, Raman spectroscopy, and SEM to characterize differences between two in situ modified electrodes NiCo 2 -O 4 @rGO-modified electrodes and wet-NiCo 2 O 4 @rGO.…”
Section: Electrochemical Detection Of Venlafaxinementioning
confidence: 99%
“…Their technique showed a successful application for determining the VEN in pharmaceutical formulations and human plasma. Ali et al did not observe any interferences from the real sample matrix [ 39 ]. Their new electrode exhibited very good reproducibility and excellent stability.…”
Section: Electrochemical Detection Of Venlafaxinementioning
confidence: 99%
See 1 more Smart Citation